MANAJEMEN PEMBELAJARAN BERBASIS KEMANDIRIAN DALAM MENINGKAT PRESTASI BELAJAR SISWA - Herman; Bakhtiar, Bakhtiar; Nur Rohman; Jamin, Hanifuddin; Suandi (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2025)
This study aims to develop independence-based learning management in improving student learning achievement. Using library research method with literature review approach in analyzing data and information about independence-based learning management in improving student learning achievement. The result of the research shows that the management of independence-based learning is implemented in ways: the first stage determines clear and specific learning objectives to improve student learning achievement, the second stage develops effective and efficient learning plans to achieve learning objectives, in the third stage uses digital technology to support the self-learning process in improving student learning achievement, the fourth stage guides and accompanies students in the self-learning process to ensure increased student learning achievement, in the fifth stage evaluates the self-learning process, and in the sixth stage develops strategies to improve student learning achievement. The findings of this study are expected to add insight to educators, and educational practitioners in developing independence-based learning management in improving student achievement.